PRIMARY EXTRANODAL NON-HODGKIN'S LYMPHOMA INVOLVING RIGHT MAXILLA - Elitsa Deliverska; Evgenii Hadjiev; Lutchezar Stefanov; Gergana Tsvetkova; Emel Bekirova; Sadeta Parusheva (Peytchinski Publishing, 2020)
Background: Lymphoma in a single bone without any nodal or visceral involvement is known as primary intra-osseous lymphoma, which is a very uncommon malignancy. It constitutes 3.1% of malignant bone tumours and 5% of extranodal lymphomas, and the incidence is only 0.6% in the jaws. These tumours can be primary or secondary (in the disseminated forms). The primary intra-osseous lymphoma of the jaws is a challenge to diagnose, because of their various clinical presentation, which can mimic an odontogenic tumour, cyst or a fibro-osseous lesion. Purpose: This case report discusses a rare malignancy of jaw bones, including clinical presentation, histopathologic features, immunologic profile, PET scan, management and prognosis. Material and methods: We present a case of a primary intraosseous lymphoma in a 45-year-old female who presented with a swelling in the right maxilla. It highlights the importance of recognizing rare entities that may present in the jaws, the impact of the disease and its management. Results: Jaw localization of Non-Hodgkin's lymphoma is rare. Clinical symptomatology and radiological signs are poorly contributive. The diagnosis relies on the histopathological analysis. Conclusion: One of the diagnostic problems with regard to NHL is the variable nature of clinical symptoms. A biopsy allowed diagnosing an intra-oral bone lymphoma, and the patient was referred to the hematooncology unit for treatment.